China's 'New Silk Roads': sub-national regions and networks of global political economy. Issue 9 (1st September 2016) - Summers, Tim
Abstract: This paper argues that the Chinese government's 'belt and road' initiative – the Silk Roads vision of land and maritime logistics and communications networks connecting Asia, Europe and Africa – has its roots in sub-national ideas and practices, and that it reflects their elevation to the national level more than the creation of substantially new policy content. Further, the spatial paradigms inherent in the Silk Roads vision reveal the reproduction of capitalist developmental ideas expressed particularly in the form of networks, which themselves have become a feature of contemporary global political economy. In other words, the Silk Roads vision is more of a 'spatial fix' than a geopolitical manoeuvre.